Effect of carbon to nitrogen ratio of food waste and short resting period on microbial accumulation during anaerobic digestion. (July 2022) - Salangsang, Maria Cecilia D.; Sekine, Mutsumi; Akizuki, Shinichi; Sakai, Hiroyuki D.; Kurosawa, Norio; Toda, Tatsuki
Abstract: The short resting period technique (i.e., deliberate stoppage of the substrate supply) for anaerobic digestion (AD) leads to accumulation of microbes using residual substrate, which could be an effective method to achieve microbial proliferation without additional investment/operating costs. The composition of substrate must influence the increase of microbes. However, even the effect of the carbon to nitrogen (C/N) ratio of substrate, a basic and important parameter in AD, on this phenomenon is unclear. This study aimed at clarifying the effect of the C/N ratio of food waste and the short resting period on microbial accumulation. Food waste was semi-continuously treated at a loading rate of 3.0 g-VS L −1 d −1 for 40 d, after which a deliberate resting period was provided. By the third day of the resting period, the cell density increased by 2.63, 2.57, 2.16, and 1.61 folds in the 13:1, 18:1, 23:1, and 31:1 C/N substrate conditions, respectively. It was revealed that food waste with a lower C/N ratio has the potential to accumulate more microbes, with nitrogen degradation increasing during the resting period. The microorganisms may have consumed the residual nitrogen-bearing protein, which has higher biomass yields than easily degradable carbohydrates. The dominant microbial community structure was almost maintained, suggesting that stable AD under higher organic loading rates could be achieved by the accumulated microbes upon feeding resumption. The short resting period technique may likewise help in reducing accumulated residual substrate, and in shortening the start-up period of methane fermentation in AD facilities. Highlights: The cell density increased by 2.6 times max by 3 days of resting period of feeding. The increase in cell density was higher with lower C/N ratio of substrate supply. Accumulated-protein decomposition contributes to the increase in microbial density. The microbial community structure is maintained during the resting period.